G372(P) Can we do more to prevent picu admissions for children presenting with severe asthma? what are the modifiable factors. (May 2019) - Opstad, HS; Mukerji, MR; Samanta, A; Klaber, R; Wood, K
Abstract : Introduction: Children should not die from asthma in the UK in the 21 st Century. Yet national data shows an average of 21.4 deaths per annum in the 5 years leading up to 2016 in 0–14 year olds 1 . We analysed the patient journey for children admitted to PICU for severe asthma over a 22 month period to identify modifiable factors which may have prevented these admissions. Aims: To identify the number of admitted children who have poor asthma control/compliance to therapy To ascertain whether children had appropriate follow up arranged on discharge Methods: Retrospective data was collected for asthma-related PICU admissions over a 22 month period. 'Snomed CT' clinical coding data was used to identify patients. The records were then analysed to collect this data. Results: There were 19 patients in total; average age: 7 years. 60% were under secondary or tertiary follow up for asthma & 11% had a documented 'active asthma plan' prior to PICU admission. 32% had documented poor compliance/control with therapy with multiple hospital attendances. 38% of children had significant co–morbidities, which may have been contributory. All patients made a good recovery and had planned follow up on discharge: 63% tertiary/32% secondary/5% primary. Device training was only documented in 37% of cases. Limitations: Reliance on correct coding of conditions. Variable quality of transfer documentation with information including past history/compliance. Conclusions: Poor compliance with therapy was identified as a key factor in anticipating PICU admission. An integrated child health approach is needed for cohesion between primary, secondary and tertiary services to fully engage with families and promote better compliance. Device training needs to be highlighted at every stage in the patient journey to reinforce importance and provide educational opportunities for families. Every child with asthma needs an asthma management plan and parents need to be able to confidently and competently manage inhaler use and technique prior to discharge from hospital and within the primary care setting. Reference: Asthma UK, 2018. Asthma data visualisations. [online]. Available from: https://www.asthma.org.uk/get-involved/campaigns/data-visualisations#Deaths [Accessed 28 September 2018]